Preparation and structural characterisation of model cellular vitreous carbon foams. (February 2017) - Letellier, M.; Szczurek, A.; Basso, M.-C.; Pizzi, A.; Fierro, V.; Ferry, O.; Celzard, A.
Abstract: The aim the present work was to produce carbon foams with as different as possible porous structures but with similar composition and carbon texture for studying precisely the influence of different structural parameters such as density, cell size or interconnectivity on the physical properties of these foams. Over 60 different cellular carbon foams were obtained by pyrolysis of phenolic-furanic rigid foams, whose structure was tailored through some changes in the formulations. The structures of all of these materials were thoroughly characterised through scanning electron microscopy (SEM) and X-Ray microtomography. Both methods proved to give very consistent results, justifying the use of the simpler one, i.e., SEM. Very broad ranges of bulk densities ( 0.015 ≤ d ≤ 0.333 g c m − 3 ) and of average cell diameters ( 100 ≤ D ≤ 5000 μ m ) were obtained. Despite these very different morphologies, elemental analysis, helium pycnometry and Raman spectroscopy studies showed that the carbon constituting the foams can be considered as identical. The results presented here should be used as a basis for the most thorough and extensive studies of physical properties of vitreous carbon foams. Graphical abstract: